Non-financial reporting of corporations - N. G. Sapozhnikova (Учёт. Анализ. Аудит)
One of the important directions in the development of modern corporate reporting is the disclosure of the sustainable development of a corporation, which involves assessing the results of operations and managing changes on the way to a sustainable economy that combines data on long-term profitability, social responsibility and care for environmental protection. Therefore, non-financial reporting is becoming the main tool for communicating the information to stakeholders about the economic, environmental, and social results of a corporation’s activities. Currently, the publication of non-financial reports is carried out by transnational and large national corporations, state and municipal organizations in many countries. In the Russian Federation, the need to promote non-financial reporting is approved by the Concept for the Development of Public Non-Financial Reporting (Concept), as a state task that defines this reporting as an element of the management system, development of communications with stakeholders, a prerequisite for increasing efficiency and strengthening corporate competitiveness. A significant impact on the development of public non-financial reporting was made by the United Nations resolution containing 17 goals in the field of sustainable development, which determines the need to develop indicators that evaluate the achievement of goals at the national and global levels and reflect the contribution of the corporation to sustainable development, which are solved in the framework of public nonfinancial reporting. Large and transnational corporations are encouraged to apply sustainable production practices and reflect information on the rational use of resources in their reports. Meaningful, complete, timely, accurate, balanced, comparable and reliable information of public non-financial reporting ensures that stakeholders make informed economic decisions about the sustainability of the corporation, the impact on the environment and society. At the state level, information from public non-financial reporting makes it possible to assess the achievement of strategic goals, the need to combine or separate the activities of sectors of society. The aim of the study was to assess the key concepts of sustainability reporting, the order and specifics of disclosure of its elements and material topics reflecting the impact of the corporation on the economy, environment and society. Among the objectives set by the authors is the assessment of the principles of this type of reporting: comparability, completeness, timeliness, and verifiability, which are closely related to those used in financial reporting. Since the calculation of separate indicators of non-financial reporting and the methodology of formation of consolidated financial reporting (participation method, joint activities, etc.) are closely related, the scope of the study includes the ways of reflecting the elements of reporting. Such scientific methods as logical, expert and substantive analyses, interpretation were used in the work. The results of the research can be used by corporate specialists in the formation of reporting in the field of sustainable development, university professors in the educational process, and other parties interested in the results of corporate activities